1995
DOI: 10.1007/bf00192634
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model for abnormal skeletal development in the lysosomal storage diseases

Abstract: Lysosomal storage diseases such as GM1-gangliosidosis are associated with skeletal abnormalities. Radiological and histological studies, both in human and corresponding animal models, indicate retarded bone formation. Since cartilage maturation leads to bone formation, we developed an in vitro system to study and compare the biological features of cartilage from dogs affected with GM1-gangliosidosis with age-matched controls. Costochondral chondrocytes were grown in monolayer and in agarose culture. Both affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There have been reports of progressive skeletal dysplasia and skeletal lesions characterised by retarded endochondral ossification in vertebral epiphyses leading to premature avascular necrosis of joints [8][9][10]. Gaucher disease, the most common of the lysosomal storage diseases, has many hallmarks of chronic inflammation related to microvascular occlusion including avascular necrosis [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…There have been reports of progressive skeletal dysplasia and skeletal lesions characterised by retarded endochondral ossification in vertebral epiphyses leading to premature avascular necrosis of joints [8][9][10]. Gaucher disease, the most common of the lysosomal storage diseases, has many hallmarks of chronic inflammation related to microvascular occlusion including avascular necrosis [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…In the same disorder, a PG‐rich ECM in gingival tissue of a patient was found [112]. Finally, concerning LSDs with prominent skeletal involvement, an alteration in PG expression was found in the cartilage of mucolipidosis and I‐cell disease patients [107,121], while a reduction in PG expression was characteristic in chondrocytes obtained from a GM 1 gangliosidosis canine animal model [106].…”
Section: Differential Expression Of Ecm Molecules In Lsdsmentioning
confidence: 86%
“…Another illustrative example of the connection between fibrous elements’ alterations and the symptomatology of a specific disease is that of GM 1 gangliosidosis. In an effort to create an in vitro model to study cartilage maturation in this group of patients, Aulthouse and Alroy have demonstrated a decrease in collagen type II expression in deficient canine chondrocytes, as opposed to normal cells [106]. This dysregulation in matrix production could represent a possible theory for the explanation of skeletal abnormalities, not only in GM 1 gangliosidosis but in other LSDs, as well, such as in I‐cell disease where a decrease in collagen fibril diameter was noticed in cultured chondrocytes [107].…”
Section: Differential Expression Of Ecm Molecules In Lsdsmentioning
confidence: 99%